Radicalization Redefined: Pakistan’s Democratic Pursuits Under Thick Populist Narratives - Malik, Zahra A.; Cheema, Ammara T. (Pakistan Languages and Humanities Review, 2024)
The aim of this research is to emphasize on the radicalization of developing extremist ideologies and belief sets in a society as opposed to the liberal convictions, fundamental rights and values under a democratic order. When Radicalization meets populism a birthing of a new order takes place that jeopardizes the liberal democratic order. Populist upsurge appeals to the masses on the mainstream media in order to make marginalized groups feel empowered, only for a radical take on diversity and pluralism. Populists seek to separate democracy and liberalism based on the notion that cultural liberalism is at odds with religion and local customs where underrepresented groups are made to feel that they are puppets in the hands of liberal elites who threaten their way of life by challenging their traditional values, altering demographics, and dislocating them economically so that they can never climb the social ladder. This study utilized a comparative case study method to analyze and synthesize similarities, patterns and differences between Pakistan Awami Tehreek’s (PAT) ‘Long March 2013’ and Tehreek-e-Labbaik Pakistan’s ‘2021 Pakistan Protests’. The findings indicate a wave of populism that has plunged Pakistan’s democratic society. It reflects the by-passing of democratic checkpoints, by people who take to the streets to get their demands addressed in light of public scrutiny, while mainstream political parties do not show concern for the populace. A society without institutional restraints legitimized by organized mobs that takes to the streets to hold the reins of power in their hands is a dangerous idea that spawns in the minds of the citizens creating polarization, uncertainty and fragmentation making governance, a difficult feat.